2012
DOI: 10.1053/j.gastro.2012.02.046
|View full text |Cite
|
Sign up to set email alerts
|

The Zinc Transporter Zip14 Influences c-Met Phosphorylation and Hepatocyte Proliferation During Liver Regeneration in Mice

Abstract: BACKGROUND & AIMS Zinc homeostasis in cells is maintained through tight regulation of zinc influx, efflux, and distribution to intracellular organelles by zinc transporters. The Zrt-Irt-like protein (ZIP) transporters facilitate zinc influx to the cytosol. Expression of the ZIP family member Zip14 can be induced by inflammatory cytokines, which also initiate liver regeneration. Hepatocyte proliferation is required for liver regeneration. Zinc regulates cell proliferation, tissue growth, and many mitogenic sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
89
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(96 citation statements)
references
References 43 publications
7
89
0
Order By: Relevance
“…Ϫ/Ϫ ) mice have been described previously (3,5,33 65 Zn was measured via ␥-scintillation spectrometry. For the antibiotic experiment, ultrapure (MiliQ, Billerica, MA) drinking water was supplemented with neomycin (0.5 mg/ml) and ampicillin (1 mg/ml) for 4 wk prior to tissue collection.…”
Section: Animals and Diets Design And Genomic Validation Of The Zip1mentioning
confidence: 99%
See 2 more Smart Citations
“…Ϫ/Ϫ ) mice have been described previously (3,5,33 65 Zn was measured via ␥-scintillation spectrometry. For the antibiotic experiment, ultrapure (MiliQ, Billerica, MA) drinking water was supplemented with neomycin (0.5 mg/ml) and ampicillin (1 mg/ml) for 4 wk prior to tissue collection.…”
Section: Animals and Diets Design And Genomic Validation Of The Zip1mentioning
confidence: 99%
“…All other primer sequences were selected using the qPrimerDepot database, http://mouseprimerdepot.nci.nih.gov/, as described in Cui et al (17). TBP mRNA was the normalizer for relative expression, as described previously (3,5).…”
Section: Animals and Diets Design And Genomic Validation Of The Zip1mentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc is a known inhibitor of PTP1B through physical binding to the enzyme (32). We previously reported that overexpression of ZIP14 in AML12 hepatocytes suppressed PTP1B activity (33).…”
Section: Discussionmentioning
confidence: 99%
“…However, increased HGF concentration may accelerate the metastasis and recurrence of liver cancer if micrometastasis is accompanied. The reason lies in HGF receptor c-Met has a high expression rate in the liver cell tissue of liver cancer (Aydemir et al, 2012), and a small amount of HGF can stimulate the growth of micrometastatic lesions.…”
Section: Discussionmentioning
confidence: 99%